Stability of Oligopoly with Product Differentiation - Hadar, Josef (Review of Economic Studies, 1966)
Journal Article Stability of Oligopoly with Product Differentiation Get access Josef Hadar Josef Hadar Case Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 1, January 1966, Pages 57–60, https://doi.org/10.2307/2296641 Published: 01 January 1966